Neuroinflammation and its role in the pathogenesis of attention deficit hyperactivity disorder (literature review) - R. F. Gasanov; I. V. Makarov; D. A. Emelina; A. S. Avtenuk (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article discusses the role of inflammatory reactions in the formation of attention deficit hyperactivity disorder (ADHD). Based on a wide and modern material, the mechanisms of development of oxidative stress with the formation of free radicals are considered, which, in turn, initiate a cascade of inflammatory reactions. Inflammation factors are analyzed in detail, biomarkers of neuroinflammation are distinguished and their role in changing the neurotransmitter balance is revealed. Biomarkers of neuroinflammation isolated from patients with ADHD give conflicting results in some particular issues, which certainly require clarification. But in general, it is found that increased inflammation in the early stages of brain development seems to be associated with the ADHD phenotype. ADHD is commonly believed to be a hereditary disease; therefore, it can be expected that patients have polymorphisms of genes associated with inflammation, which is illustrated in a wide range of material. In addition, the problems of inducing neuroinflammation with traditional drugs for the treatment of ADHD: methylphenidate and atomoxetine are considered. The prospects of developing algorithms for the diagnosis and treatment of attention deficit hyperactivity disorder are noted.